Review methods: we cannot trivialize them - Ana Fátima Carvalho Fernandes; Cristina Maria Galvão (Universidade Federal do Ceará, 2013)
As an editorial board member and/or ad hoc consultant for journals, we perform screening or assessment of review articles and we are constantly faced with inadequacies on the classification of review methods. Therefore, the need to clarify the origin and the scientific rigor of review methods.